(untitled) (Research, Society and Development, 2022)
This study sought to understand the Mental Health Referral and Counter-Referral system from the perspective of physicians of primary health care (PHC). To do so, a qualitative approach with an exploratory focus was adopted, and interviews were conducted with physicians working in PHC in a city in the state of Alagoas, Brazil. The collected and produced data were treated using content thematic analysis. In this context, the Reference and Counter-Reference system was recognized as a form of dialogue between the components of the care network, especially the Psychosocial care network, however, there is a mostly negative perception about its operation, given situations such as the difficulty of dialogue between the PHC medical professional and the psychiatrist, as well as the performance of the patient as a channel or vehicle of communication between the network, in view of the absence of an instrument that performs this function properly. Thus, it is necessary to think of ways to make the Referral and Counter-Referral system more efficient, in order to provide a greater possibility for the development of integral care in mental health.